The prenatal verification of the obstructive uropathy at the fetal - M.L. Chekhonatskaya (Саратовский научно-медицинский журнал, 2010)
The research goal is to study functional condition of upper and lower urinary tracts at fetus with obstructive uropathy and development of differential diagnostic and prognostic criteria of transition of functional disorders to organic. The diagnosis of prenatal and verified postnatal obstructive uropathy at 42 fetuses has been made by prenatal ultrasonic cystometry. Process of filling and evacuation of bladder has been under study. Obtained data have been compared with the results of dynamic measurement of kidney sizes in a standard projection. According to the results only at 19,1% of cases statistically significant urodynamic differences have not been revealed in comparison with control group. Diagnostic accuracy of organic form of urodynamic obstructions is 84%, of functional in 64,7% of observations and in 52,9% of cases the infection of urinary tracts with incomplete evacuation of bladder has been diagnosed. The degree of kidney and ureter expansion is not a differential diagnostic criterion of organic or functional urodynamic obstructions. However, using a principle of estimation of upper and lower urinary tracts condition, it is possible to make a prenatal differential diagnosis of variants of defects